(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Heritages are nonexistent and existent asset of a community that are important for historical, economic educational, recreational, social, and cultural significance, conserved and handed over from one generation to another. The utilization of heritage sites’ resources for social, economic and cultural benefits in some countries have been extensively studied. This paper presents the overview of heritage sites benefits on social, economic and cultural benefits in Nigeria. A qualitative approach through a synthesis of literature was adopted in the study. This review provides details to further develop deeper understanding of heritage resources for social, economic and cultural advancement in Nigeria. Empirical studies are cited to elaborate on the importance of heritage resources to sustainable development. Findings of the research revealed moderate contributions of heritage sites resources to sustainable development in Nigeria. The need to encourage communities’ participations and development of domestic tourism for heritage sites was maintained in the paper. The study concluded that for there to be development of heritage resources that will drive socio-economic and cultural growth, the protection of the resources is of utmost important.